Rethinking Urban Female Adolescents' Safety Net: The Role of Family, Peers, and Sexual Partners in Social Support - Robinson, Camille A. (Am J Health Promot, 2019)
PURPOSE: To examine how interpersonal factors are associated with family, peer, and partner social support among urban female adolescents in sexual relationships. DESIGN: Secondary data analysis of cross-sectional data. SETTING: Two urban health clinics and community sites in Baltimore, Maryland. SUBJECTS: 116 female adolescents (ages 16-19) with 131 heterosexual relationships from the Perceived Risk of Sexually Transmitted Diseases cohort. MEASURES: Interpersonal factors included parental monitoring, friend-partner connectedness, and feelings of intimacy for partner. Social support was measured using the Multidimensional Scale of Perceived Social Support with family, peer, and partner subdomains. ANALYSIS: Multivariable linear regression models using baseline data and accounting for clustering of partners. RESULTS: Adolescents perceived high levels of family, peer, and partner support with the greatest coming from partners [range 1-5; family mean 4.0 (95%CI:3.83,4.18); peer mean 4.2 (95%CI:4.05,4.33); partner mean 4.5 (95%CI:4.36,4.60)]. Parental monitoring and friend-partner connectedness were significantly associated with greater family (b=0.11, SE=0.03, p=0.001; b=0.15, SE=0.06, p=0.02) and peer support (b=0.06, SE=0.02, p=0.01; b=0.29, SE=0.07, p<0.001). Feelings of intimacy for partner was significantly associated with greater partner support (b=0.08, SE=0.03, p=0.02). CONCLUSION: Feeling connected to one’s social network and having a connected network is an important contribution to social support for urban female adolescents in sexual relationships. Future research targeting interpersonal factors is warranted as it may result in increased social support and promote positive sexual health behaviors in an urban female adolescent population.